PLURALISME AGAMA DAN KONFLIK - Priyono Priyono (Analisa: Journal of Social Science and Religion, 2008)
Indonesians generally claim as religious nation. History showedthat Indonesian is a nation with rich races, tribes, ethnics, cultures, custom, and religions. That richness is a gift from God so human beingscould organize and maintain their harmony in order to respect and appreciate one another in their diversity.Religions and beliefs such as Islam, Christian, Catholics, Hinduism, Buddha and other believe ideologies educate human beings to dogood things (ikhsan) among human being, between members of a religious community, and among members of various religious communities.Efforts needed to keep away tension and conflict in daily life ofmembers of a religious community and among members of various religious communities are to implement and to apply their own tenets, tocreate dialog among various religious community in leader level or ingrassroots level regularly. In addition, to collect various thoughts andopinions of different group of people that care of religious role in solving current social problems.